Nutritional Value of Pulses and Whole Grains (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Pulses and whole grains have a rich history as part of healthy and sustainable dietary patterns. There is ongoing interest in the use of these foods, and their ingredient derivatives, to delineate effects on multiple aspects of human health and quantify their individual and societal benefits. In additional to an editorial synopsis, this Special Issue “Nutritional Value of Pulses and Whole Grains” adds 11 manuscripts, including 7 studies, 2 reviews, and 2 communications that touch on a variety of topics including the efficacy of pulses and whole grains on cardiometabolic risk factors, consumer preferences and the changing retail landscape, effects on health and societal economic outcomes, and a proposed consensus to effectively integrate and evaluate whole grains and pulses within dietary patterns. The works presented herein touch on various topics and themes that are relevant to a changing food landscape aimed at incorporating more pulses and whole grains into diets. They identify near and future benefits of pulses and whole grains on health, but also underscore some of the underlying challenges around their dietary incorporation. The latter could be critical for leveraging whole grains and pulses in a manner that aligns with global dietary objectives.